Hydrogen‐Atom Transfer Oxidation with H2O2 Catalyzed by [FeII(1, 2‐bis(2, 2′‐bipyridyl‐6‐yl)ethane(H2O)2]2+: Likely Involvement of a (μ‐Hydroxo)(μ‐1, 2‐peroxo)diiron(III) Intermediate. Issue 10 (13th September 2017) - Khenkin, Alexander M.; Vedichi, Madhu; Shimon, Linda J. W.; Cranswick, Matthew A.; Klein, Johannes E. M. N.; Que, Lawrence; Neumann, Ronny
Abstract: The iron(II) triflate complex (1 ) of 1, 2‐bis(2, 2′‐bipyridyl‐6‐yl)ethane, with two bipyridine moieties connected by an ethane bridge, was prepared. Addition of aqueous 30 % H2 O2 to an acetonitrile solution of1 yielded2, a green compound with λmax =710 nm. Moessbauer measurements on2 showed a doublet with an isomer shift (δ) of 0.35 mm/s and a quadrupole splitting (Δ E Q ) of 0.86 mm/s, indicative of an antiferromagnetically coupled diferric complex. Resonance Raman spectra showed peaks at 883, 556 and 451 cm −1 that downshifted to 832, 540 and 441 cm −1 when1 was treated with H2 18 O2 . All the spectroscopic data support the initial formation of a (μ‐hydroxo)(μ‐1, 2‐peroxo)diiron(III) complex that oxidizes carbon‐hydrogen bonds. At 0 °C2 reacted with cyclohexene to yield allylic oxidation products but not epoxide. Weak benzylic C−H bonds of alkylarenes were also oxidized. A plot of the logarithms of the second order rate constants versus the bond dissociation energies of the cleaved C−H bond showed an excellent linear correlation. Along with the observation that oxidation of the probe substrate 2, 2‐dimethyl‐1‐phenylpropan‐1‐ol yielded the corresponding ketone but no benzaldehyde, and the kinetic isotope effect, kH /kD, of 2.8 found for the oxidation of xanthene, the results support the hypothesis for a metal‐based H‐atom abstraction mechanism. Complex2 is a rare example of a (μ‐hydroxo)(μ‐1, 2‐peroxo)diiron(III) complex that can elicit the oxidation of carbon‐hydrogen bonds. Abstract :